Density and isothermal compressibility of supercritical H2O–NaCl fluid: molecular dynamics study from 673 to 2000 K, 0.2 to 2 GPa, and 0 to 22 wt% NaCl concentrations. Issue 1 (2nd April 2015) - Sakuma, H.; Ichiki, M.
Abstract: We report on molecular dynamics (MD) simulations for predicting the density and isothermal compressibility of an H2 O–NaCl fluid as a function of temperature (673–2000 K), pressure (0.2–2.0 GPa), and salt concentration (0.0–21.9 wt%). The atomistic behavior was analyzed via the hydration number of ions and number of ion pairs. Hydration numbers of Na + and Cl − increased with increasing pressure and decreasing temperature. Conversely, the fraction of Na–Cl ion pairs increased with decreasing pressure and increasing temperature. This hydration and association behavior is consistent with the low dielectric constant of H2 O under these conditions. The presence of polynuclear clusters of Na–Cl was confirmed at high temperatures, low pressures, and high salt concentrations. We propose a purely empirical equation of state (EoS) for H2 O–NaCl fluids under high temperatures and pressures that should be useful for estimating the fluid distribution in Earth's crust and upper mantle in relation to effects on earthquakes and volcanic eruptions. Abstract : We report on molecular dynamics (MD) simulations for the density and isothermal compressibility of H2 O–NaCl fluids as a function of temperature (673–2000 K), pressure (0.2–2.0 GPa), and salt concentration (0.0–21.9 wt%). The presence of polynuclear clusters of Na–Cl ion pairs was confirmed at high temperatures, low pressures, and high salt concentrations. Purely empirical EoS for the density and isothermal compressibility were proposed for these fluids over a wide range of pressures (0.2–2.0 GPa), temperatures (673–2000 K), and salt concentrations (0–21.9 wt%).